Analysis of risk factors in patients with leukoaraiosis. Issue 8 (February 2017) - Guan, Jiaxin; Yan, Chaoqi; Gao, Qiang; Li, Jun; Wang, Li; Hong, Ming; Zheng, Xiuhai; Song, Zhiqiang; Li, Mei; Liu, Meiling; Fan, Ying; Ma, Lan
Abstract : Abstract: To investigate the risk factors for leukoaraiosis (LA) and the correlation between risk factors and LA. The study comprised 92 patients with diagnoses of LA (LA group) and 56 non-LA individuals (control group). Data were collected for the following: age, gender, fasting blood glucose, total cholesterol, triglyceride, high- and low-density lipoprotein cholesterol, uric acid, creatinine, and histories of smoking, hypertension, and diabetes. Levels of serum asymmetric dimethylarginine (ADMA) were detected by enzyme-linked immunosorbent assay. Univariate analysis showed statistical significance between the 2 groups in age, histories of hypertension and smoking, uric acid, creatinine, and levels of serum ADMA ( P  < 0.05). Binary logistic analysis showed that age ( P  < 0.0001), hypertension ( P  = 0.0101), and serum ADMA ( P  = 0.0206) were related to LA. Pearson correlation analysis showed that levels of serum ADMA correlated with uric acid ( r  = 0.184, P  = 0.025) and creatinine ( r  = 0.169, P  = 0.04). Age, hypertension, and levels of serum ADMA were independent risk factors for LA. Serum ADMA levels may be related to uric acid and creatinine.